Immunogenicity of a Multi-Epitope DNA Vaccine Encoding Epitopes from Cu–Zn Superoxide Dismutase and Open Reading Frames of Brucella abortus in Mice - Escalona, Emilia; Sáez, Darwin; Oñate, Angel (Frontiers in Immunology, 2017)
Brucellosis is a bacterial zoonotic disease affecting several mammalian species that is transmitted to humans by direct or indirect contact with infected animals or their products. In cattle, brucellosis is almost invariably caused by Brucella abortus. Live, attenuated Brucella vaccines are commonly used to prevent illness in cattle, but can cause abortions in pregnant animals. It is therefore desirable to design an effective and safer vaccine against Brucella. We have used specific Brucella antigens that induce immunity and protection against B. abortus. A novel recombinant multi-epitope DNA vaccine specific for brucellosis was developed. To design the vaccine construct we employed bioinformatics tools to predict epitopes present in Cu-Zn superoxide dismutase and in the open reading frames of the genomic island-3 (BAB1_0260, BAB1_0270, BAB1_0273 and BAB1_0278) of Brucella. We successfully designed a multi-epitope DNA plasmid vaccine chimera that encodes and expresses 21 epitopes. This DNA vaccine induced a specific humoral and cellular immune response in BALB/c mice. It induced a typical T-helper (Th) 1 response, eliciting production of immunoglobulin G2a (IgG2a) and IFN-γ particularly associated with the Th1 cell subset of CD4+ T cells. The production of IL-4, an indicator of Th2 activation, was not detected in splenocytes. Therefore, it is reasonable to suggest that the vaccine induced a predominantly Th1 response. The vaccine induced a statistically significant level of protection in BALB/c mice when challenged with B. abortus 2308. This is the first use of an in silico strategy to a design a multi-epitope DNA vaccine against B. abortus.